Effects of Hydrogen on Acceptor Activation in Ternary Nitride Semiconductors. (9th February 2017) - Fioretti, Angela N.; Stokes, Adam; Young, Matthew R.; Gorman, Brian; Toberer, Eric S.; Tamboli, Adele C.; Zakutayev, Andriy
Abstract : Enhanced acceptor activation is achieved in the ternary nitride semiconductor ZnSnN2 . Hydrogen passivation of acceptors during growth, coupled with post‐growth annealing to remove hydrogen, suppresses native donor formation and moves the Fermi energy away from the conduction band minimum. This technique produces nondegenerate zinc tin nitride with 10 16 cm −3 electron concentration.